The adult learner : the definitive classic in adult education and human resource development - Knowles, Malcolm S. 1913-1997; Holton, Elwood F., 1957-; Swanson, Richard A., 1942- (Routledge, 2015)
"How do you tailor education to the learning needs of adults? Do they learn differently from children? How does their life experience inform their learning processes? These were the questions at the heart of Malcolm Knowles' pioneering theory of andragogy which transformed education theory in the 1970s. The resulting principles of a self-directed, experiential, problem-centred approach to learning have been hugely influential and are still the basis of the learning practices we use today. Understanding these principles is the cornerstone of increasing motivation and enabling adult learners to achieve. The 8th edition of The Adult Learner has been revised and updated. Holton and Swanson have enlivened the latest edition in terms of content and style. The new supporting website and added chapter level reflection questions make this latest edition more accessible than ever. This new edition includes: Updates to the book to reflect the very latest advancements in the field. Addition of two new chapters: on related cutting edge realms, Neuroscience & Learning and Information Technology & Learning. Creation of a supporting website: This website for The Adult Learner 8th Edition will provide basic instructor aids. For each chapter there will be a PowerPoint presentation, learning exercises, and added study questions. Revisions throughout to make it more readable and relevant to your practices. If you are a researcher, practitioner or student in education, an adult learning practitioner, training manager, or involved in human resource development, this is the definitive book in adult learning you should not be without"- Resumé vydavatel